Peranan Bpbd Dalam Penanggulangan Bencana Alam Di Desa Windurejo Kecamatan Kesesi Kabupaten Pekalongan - Kusumajati, Luthfiana, Dra. Hj. Sri Arfiah, S.H., M.Pd (2016)
Objective Research to determine the role of BNPB in disaster management in the village Windurejo Kesesi District of Pekalongan. Method of this study is a qualitative description of the survey conducted by the BPBD Pekalongan. Methods of data collection were interviews and observations to obtain data BPBD role in disaster management. Documentation used to collect data on the condition Village area WindurejoKesesi District of Pekalongan. Data validation was done using data triangulation technique. Data were analyzed using an interactive model. The survey results revealed the presence of BPBD as the main actors in disaster management in the village Windurejo already known by the public. During this time BPBD role in disaster relief starting from before the disaster, emergency response (during a disaster) and post-disaster. BPBD role in disaster management is related to its role as a coordinator. All coordination in disaster response conducted by BPBD so that all goes well. Factors that inhibit BPBD role in disaster management is the support of local governments and support agencies and organizations supporting disaster relief. Factors that inhibit BPBD role in disaster management is human resource that supports many are not competent and infrastructure is not yet adequate.